2006
DOI: 10.1074/jbc.m511945200
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Biological Functions of Drosophila Histone Deacetylases by RNA Interference and Transcriptional Profiling

Abstract: Chromatin modifications such as acetylation, methylation, phosphorylation, ubiquitination, and sumoylation of histones play an important role in the regulation of transcription (1-5). Together with DNA methylation, these modifications are part of a broad and multifaceted strategy whereby eukaryotes regulate gene expression at the epigenetic level (6 -8).Acetylation of histones is tightly controlled by the activity of histone acetyltransferases and histone deacetylases (HDACs) 2 (9, 10). Histone deacetylation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 49 publications
6
84
0
Order By: Relevance
“…Examining the recruitment of different factors on endogenous promoters, it was observed that both N-CoR/HDAC3 and the NuRD complex were recruited by tamoxifen-complexed ER, but in a sequential manner, following a strict choreography of events (Liu and Bagchi, 2004). The distinct functions of different HDACs and HDAC complexes are also suggested by overexpression/downregulation studies as well as developmental profiling of individual HDACs in Drosophila (Cho et al, 2005;Foglietti et al, 2006). Such studies reveal unique sets of genes regulated by each enzyme.…”
Section: Diverse Biological Functions Of Hdac3mentioning
confidence: 92%
See 1 more Smart Citation
“…Examining the recruitment of different factors on endogenous promoters, it was observed that both N-CoR/HDAC3 and the NuRD complex were recruited by tamoxifen-complexed ER, but in a sequential manner, following a strict choreography of events (Liu and Bagchi, 2004). The distinct functions of different HDACs and HDAC complexes are also suggested by overexpression/downregulation studies as well as developmental profiling of individual HDACs in Drosophila (Cho et al, 2005;Foglietti et al, 2006). Such studies reveal unique sets of genes regulated by each enzyme.…”
Section: Diverse Biological Functions Of Hdac3mentioning
confidence: 92%
“…Such studies reveal unique sets of genes regulated by each enzyme. Surprisingly, similar numbers of genes were found to be repressed and activated in each case, perhaps through both direct and indirect effects (Cho et al, 2005;Foglietti et al, 2006).…”
Section: Diverse Biological Functions Of Hdac3mentioning
confidence: 92%
“…Foglietti et al performed genome-wide expression analysis upon HDAC1, 2, 3, 4 and X depletion, but surprisingly only found significant changes in gene expression for HDAC1 and HDAC3 knock-down (Foglietti et al, 2006). We therefore compared our expression data to the effect of depleting those two HDACs.…”
Section: Cooperation Of Dtip60 and Hdac1 In Gene Repressionmentioning
confidence: 96%
“…RNAi and TSA treatment as determined by (Foglietti et al, 2006). We asked if there is an overlap of respective subgroups based on flybase numbers.…”
Section: Bioinformaticsmentioning
confidence: 99%
See 1 more Smart Citation